2003
DOI: 10.1042/bst0310384
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine-reduced diet in metastatic hormone-refractory prostate cancer (HRPC) patients

Abstract: Polyamine (PA) deprivation is effective in prostate carcinoma models. We have assessed the observance by patients, tolerance and side effects of a PA-reduced diet (PRD) and intestinal decontamination (ID), in order to reduce PA dietary and intestinal bacterial pools, in metastatic, hormone-refractory prostate cancer (HRPC) patients. A total of 13 volunteers (mean age, 67+/-10 years) with metastatic HRPC were proposed for PRD and ID (0.75 g/day of oral neomycin every other week). The mean time from HRPC diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Even without considering the difference in metabolic rates between mice and humans, our results suggest that certain sources of dietary putrescine could reach levels capable of modifying sulindac responses in humans. Our data add to the growing recognition of the potential importance of dietary polyamines for their effects on cancer progression (52,53). (A) Effect of sulindac on steady-state levels of spermidine/spermine N 1 -acetyltransferase (SSAT) RNA in the small intestine of wild-type Apc (Apc +/+ ) and Apc Min/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Even without considering the difference in metabolic rates between mice and humans, our results suggest that certain sources of dietary putrescine could reach levels capable of modifying sulindac responses in humans. Our data add to the growing recognition of the potential importance of dietary polyamines for their effects on cancer progression (52,53). (A) Effect of sulindac on steady-state levels of spermidine/spermine N 1 -acetyltransferase (SSAT) RNA in the small intestine of wild-type Apc (Apc +/+ ) and Apc Min/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have shown that polyamine deficient chow, along with concomitant administration of inhibitors of polyamine synthesis and/or antibiotics that suppress intestinal flora, lowers overall blood polyamine concentrations ( 6 ). In patients with malignancies, whose blood polyamine levels are often increased, reduced polyamine intake decreases blood polyamine concentration ( 10 ).…”
mentioning
confidence: 99%
“…As previously shown by Bardocz et al, 43 some food ingredients contain large quantities of polyamines and preliminary clinical trials performed in metastatic hormone-refractory prostate cancer patients have revealed the feasibility of a nutrition therapy based upon a 6-month polyamine-reduced diet. 44,45 In conclusion, it is worth pointing out that the production process is very cheap and, by not involving organic solvents surfactants or particular capping strategies, it can be considered a "green chemistry" product. Nevertheless, the favorable magnetic properties of the material are guaranteed by optimizing the magnetic material/organic shell ratio.…”
Section: Discussionmentioning
confidence: 99%